Economic valuation of land uses in Oudomxay Province, Lao PDR: Can REDD+ be effective in maintaining forests? - Wong, Grace Y.; Darachantara, S; Soukkhamthat, T. (MDPI, 2014)
The rapid economic growth in Lao PDR over the last two decades has been driven by the natural resource sectors and commercialization in the agriculture sector. Rural landscapes are being transformed over the past decade from land use mosaics of subsistence and smallholder farms to large-scale plantations dominated by a few commercial crops. The capacity of these commercial agriculture plantations to alleviate rural poverty, part of the Government of Lao PDR’s national development policy, is increasingly weighed against its long-term impacts on ecosystem services and sustainability of land and forest resources. We used an extended cost-benefit approach (CBA) to integrate certain environmental elements to traditional financial analysis for a comparative look at four land use systems in the northern part of the country. The CBA results demonstrate that commercial agriculture (maize and rubber plantations) does have the potential to support poverty alleviation in the short-run. It, however, exposes the land to serious environmental risks. By comparison, the traditional land uses studied (upland rice farming and non-timber forest products collecting) are largely subsistence activities that are still considered as sustainable, though this is increasingly affected by changing market and population dynamics. The results suggest that longer-term environmental costs can potentially cancel out short-term gains from the commercialization to mono-crop agriculture. Incentives for conserving ecosystem services (such as the Reducing Emissions from Deforestation and forest Degradation (REDD+) mechanism) may have a potential role in supporting diversification of traditional livelihoods and increasing the competitiveness of maintaining forests.